Do economic recessions cause inequality to rise? - Maximo Camacho; Gonzalo Palmieri (Journal of Applied Economics, 2019)
We use a local projection approach to analyze the effect of economic recessions on income inequality in a comprehensive sample of 43 countries from 1960 to 2016. Although we consider both business-cycle and growth-cycle recessions, we fail to find evidence of significant positive impacts of economic downturns on income distribution, once controls are added to the model. However, we do find important differences across countries, which mainly depend on the degree of economic development.
Keywords: 330; Economic cycles; income inequality; local projections